Rearranging the furniture: A blueprint for reappropriating fixed resources to create an emergency department resuscitative care unit - Angela Barskaya; Liliya Abrukin; Christopher McStay (Journal of the American College of Emergency Physicians Open)
Abstract Emergency department (ED) care teams face challenges in providing timely, high‐quality care to critically ill patients because of competing patient care priorities and a multitude of system strains, including patient boarding. Patients who are boarding in the ED experience increased morbidity and mortality, and this is particularly true for those who are critically ill. Geography‐based models for critical care delivery in the ED range from resuscitation bays to full‐fledged ED intensive care units. Studies have shown that such models can improve patient survival without affecting cost. Here, we describe how we reappropriated limited fixed resources to create a critical care resuscitation unit in a busy, urban, academic ED. Our objective is to provide a blueprint for similar models, paying particular attention to operations, clinical care, education, and financial stability.